TINJAUAN TERHADAP KONSEP PENDIDIKAN MENURUT MUHAMMAD IQBAL - Helmi, Jon (STAI Hubbulwathan Duri, 2017)
In the concept of education according toMuhammad Iqbal ( Pakistani Philosopher who many engaged in the field of education ). Starting that human education should reflect the human nature itself. According to Muhammad Iqbal education must make people aware that there are two main self-worth in itself, namely sinsitivitas (sensitivity) and strength of self. The nature of senaitifitas means every child has to know the truth that is in him being born from birth. Then the nature of self power means that every child has a self reinforcing character to hold and translate the truth that is already in.